The Influence of Ecological Factors on the Transmission and Stability of Avian Influenza Virus in the Environment - Hewajuli, Dyah Ayu; Dharmayanti, NLP I (Indonesian Animal Sciences Society, 2014)
Ecology is a science studying the correlation among organisms and some environmental factors. Ecological factors play an important role to transmit Avian Influenza (AI) virus and influence its stability in the environment. Avian Influenza virus is classified as type A virus and belong to Orthomyxoviridae family. The virus can infect various vertebrates, mainly birds and mammals, including human. Avian Influenza virus transmission can occur through bird migration. The bird migration patterns usually occur in the large continent covers a long distance area within a certain periode hence transmit the virus from infected birds to other birds and spread to the environment. The biotic (normal flora microbes) and abiotic (physical and chemical) factors play important role in transmitting the virus to susceptible avian species and influence its stability in the environment. Disinfectant can inactivate the AI virus in the environment but its effectivity is influenced by the concentration, contact time, pH, temperature and organic matter.Â Key words: Avian Influenza, stability, transmission, ecological factors